FINDEV (FISH FINDER AND VISUAL IMAGING REMOTE UNDERWATER VEHICLE) INOVASI ROBOT BAWAH AIR UNTUK MELAKUKAN PENCITRAAN VISUAL DAN PENJEJAK IKAN - Good Rindo; Samuel Samuel; Saefulloh Misbahudin; Tomi Ahmad Maulana; Mohamad Nur Aulia (JURNAL INTEGRASI, 2020)
Indonesia has natural resources, especially abundant fisheries resources, but in reality these fisheries resources are still unable to be mapped so that fishermen still find it difficult to find fishing grounds. The author makes a prototype of Findev (Fish Finder and Visual Imaging Remote Underwater Vehicle) which is an underwater vehicle capable of performing visual imaging and tracking fish. Findev applies ROV technology or Remotely Operated Vehicle and the principle of hydrostatic equilibrium. Findev has dimensions of total length of 535.5 mm, total width of 304.2, and height of 248 mm. Findev uses a framework made of nylon material which has a tensile strength of 700 - 850 kgf / cm2. Findev has a displacement of 12.1 with a density of 1,599 g / cm3. Capable of operating at a depth of 20 m with a hydrostatic pressure of 200.1 Mpa and a downward force of 118.58 N. With a 1100 GPH bilge pump motor and an average power of 56.72 Watt, Findev can last for 1 hour operating in water . The sonar system is supported by the VT-FF001 sonar ventrior which has a range of 325 feet